URTICARIAL ADVERSE DRUG REACTIONS TO ACE INHIBITORS AND BETA-BLOCKERS - T. Gancheva; M. Ganeva; E. Hristakieva (Trakia Journal of Sciences)
PURPOSE. To evaluate the incidence of urticarial adverse drug reactions (ADRs) to ACE inhibitors and beta-blockers, patient demographics, drug causality, and treatment outcome. METHODS. An epidemiological study including 154 patients with urticarial ADRs, out of a total of 3554 hospitalized patients in the Clinic of Dermatology and Venereology, for a 7-year period. ADRs were defined according to the WHO and the Naranjo algorithm was used for case drug causality assessment. RESULTS. Urticarial ADRs were found in 4,1% of the study population (≥ 18 years), the average age was 50,2 years, and female prevalence was established. Concomitant cardiovascular diseases were found in 45,2% of the patients and 30,1% declared using ACE inhibitors and/or beta-blockers. The suspected drug was withdrawn, and alternative therapy was recommended by a cardiologist. The Naranjo algorithm showed 4.5% “definitive”, 45,5% “possible”, and 50% “probable” urticarial ADRs. Systemic antihistamines were administered to all patients and single short corticosteroid courses were added in 81,8%. Clinical recovery was achieved in 59% of the patients and improvement in 41%. CONCLUSIONS. The need for drug therapy and hospitalization in severe cases of urticarial ADRs to ACE inhibitors and beta-blockers are factors contributing to the overall socio-economic burden of ADRs.